Іван-Юліан Шпитковський та його курс лекцій зі сфрагістики - Целуйко, О. (Спеціальні історичні дисципліни: питання теорії та методики, 2019)
Автор розповідає про діяльність українського історика Іван-Юліана Шпитковського (1880–1969), котрий у 1950-х рр. читав курс сфрагістики студентам Львівського університету. Проаналізовано програму та курс лекцій цього курсу. Розповідається про діяльність І. -Ю. Шпитковського на посаді завідувача Музею нумізматики, сфрагістики та геральдики (1949–1959) та кабінету допоміжних історичних дисциплін Львівського університету (1959–1960). Ivan-Julian Shpytkovsky and his lectures of sphragistics (sigillography). The author tells about the activities of Ukrainian historian Ivan Julian Shpytkovsky (1880–1969). He was previously known as a researcher of the «haidamacas» movement, Ukrainian heraldic and genealogy. After II World War he came to live in Lviv, and soon he was asked to work at Ivan Franko Lviv State University. After a few years he was appointed a chief of the Museum (later, in 1959 — Cabinet) of Numismatic and Sphragistics. In this post he had to start work to organize and descriptin of the collection of seals that were kept in this Museum (Cabinet). Also Ivan-Julian Shpytkovsky taught sphragistics (sigillography) to students of Lviv University in the 1950s. The author analyzed the program and text of lectures of this course. A remarkable feature of these lectures was that І. Shpytkovsky wanted to include the Ukrainian component in this course, providing a holistic view of the development of Ukrainian sphragistics. It was very difficult to do it for him, considering the state of development of the Ukrainian sphragistics. The history of the ancient Rus’ sphragistics was presented traditionally, singling out seals of princes, clergy and private individuals. He gave a significant place in his lectures to the seals of the Principality of Galicia-Volhynia, emphasizing significant Czech-Hungarian and German influences on their development. Talking about Ukrainian sphragistics of the following centuries, I. Shpyt kovsky separated East-Ukrainian and Western-Ukrainian sphragistics materials. A characteristic feature of West-Ukrainian seals is their heraldic type, that was sighted on the West-European seals. On the other hand, a characteristic feature the East Ukrainian seals (mainly the seals of the Hetmanate, especially the Cossacks) is their symbolic and individual character. The texts of lectures on sphragistics by Ivan-Julian Shpytkovsky initiated a new tradition – the creation of Ukrainian-language textbooks on auxiliary (special) historical disciplines.